ITIL® 4 Foundation Revision Guide. - LIMITED, AXELOS (London : The Stationery Office Ltd, 2019)
ITIL® 4 has evolved from the previous, ITIL v3, version by re-shaping much of the established ITSM practices in the wider context of customer experience, value streams and digital transformation, as well as embracing new ways of working such as Lean, Agile, and DevOps.
Intro -- Copyright Page -- Contents -- Foreword -- Acknowledgements -- About this guide -- 1 Introduction -- 1.1 IT service management in the modern world -- 1.2 ITIL 4 -- 1.3 Structure and benefits of ITIL 4 -- 2 Key concepts of service management -- 2.1 Key definitions -- 2.2 Creating value with services -- 2.3 Service relationships -- 3 The ITIL guiding principles -- 3.1 The nature of the guiding principles -- 3.2 Use of guiding principles -- 4 The four dimensions of service management -- 4.1 Organizations and people -- 4.2 Information and technology -- 4.3 Partners and suppliers -- 4.4 Value streams and processes -- 4.5 External factors -- 5 The ITIL service value system -- 5.1 Purpose -- 5.2 Overview of the SVS -- 6 Service value chain -- 6.1 Purpose -- 6.2 Overview of the service value chain -- 7 ITIL management practices -- 7.1 Purpose statements -- 7.2 Definition of terms -- 7.3 Understanding the ITIL management practices -- 8 Taking the Foundation examination -- 8.1 Purpose of the ITIL 4 Foundation examination -- 8.2 Examination overview -- 8.3 Question types -- 8.4 Examination modalities -- 9 The ITIL 4 certification scheme -- 9.1 ITIL Foundation -- 9.2 ITIL Managing Professional stream -- 9.3 ITIL Strategic Leader stream -- 9.4 ITIL Master -- 9.5 ITIL and the T-shaped individual -- 10 ITIL 4 Foundation syllabus -- Further information.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: ITIL (Information technology management standard)--Examinations--Study guides; Electronic books